2018
DOI: 10.1007/s11064-018-2494-y
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin Prevents SH-SY5Y Cells from Rotenone-Induced Apoptosis via the PI3K/Akt/GSK-3β/CREB Signaling Pathway

Abstract: In addition to its original application for treating tuberculosis, rifampicin has multiple potential neuroprotective effects in chronic neurodegenerative diseases including Parkinson's disease (PD) and Alzheimer's disease. Inflammatory reactions and the PI3K/Akt pathway are strongly implicated in dopaminergic neuronal death in PD. This study aims to investigate whether rifampicin protects rotenone-lesioned SH-SY5Y cells via regulating PI3K/Akt/GSK-3β/CREB pathway. Rotenone-treated SH-SY5Y cells were used as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Tunicamycin has been reported to increase caspase-4 activity [ 18 , 58 ] and reduce the viability of SH-SY5Y cells [ 16 , 61 ]. We therefore measured cell viability of the cultured SH-SY5Y cells using CCK-8, a widely used assay that can sensitively measure the viability of a variety of cultured cells including SH-SY5Y cells [ 10 , 56 ]. We found that inhibition of caspase-4 via siRNA-caspase-4 also significantly increased cell viability after tunicamycin treatment in parallel with reduction of cytoplasmic accumulation of endogenous TDP-43 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tunicamycin has been reported to increase caspase-4 activity [ 18 , 58 ] and reduce the viability of SH-SY5Y cells [ 16 , 61 ]. We therefore measured cell viability of the cultured SH-SY5Y cells using CCK-8, a widely used assay that can sensitively measure the viability of a variety of cultured cells including SH-SY5Y cells [ 10 , 56 ]. We found that inhibition of caspase-4 via siRNA-caspase-4 also significantly increased cell viability after tunicamycin treatment in parallel with reduction of cytoplasmic accumulation of endogenous TDP-43 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It utilizes tetrazolium-8-[2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium] monosodium salt that produces a water-soluble formazan dye in living cells. The amount of this dye is directly proportional to the number of living cells, offering a sensitive assay to detect viability of many cell lines including SH-SY5Y cells [ 10 , 56 ]. Briefly, SH-SY5Y cells were transfected with siRNA for 48 h and then treated with tunicamycin (1 μg/ml) for 12 h. An equal number of 100 µl SH-SY5Y cell suspension (1 × 10 4 cells/100 µl/well) was dispensed in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…SB exerts its neuroprotective activity via both anti-apoptotic and anti-oxidative stress pathways, and in this regard, PI3K/Akt, ERK, and P38 have been widely discussed as relevant anti-apoptotic pathways in previous PD-related research. The PI3K/Akt pathways play a crucial role in dopaminergic cell survival in PD [27,45], and, therefore, molecules such as rifampicin and resveratrol that act via PI3K/Akt pathways have been investigated as potential therapeutic agents in in vitro models of PD [46,47,48]. Wu et al reported that treatment with 10 μM rifampicin could significantly inhibit rotenone-induced cell apoptosis via activation of the PI3K/Akt pathway [48], and systemic treatment with rifampicin was neuroprotective in a murine PD model [49].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GSK‐3β is considered a therapeutic target for a variety of nervous system diseases. Some studies using in vivo or in vitro models indicate that GSK‐3β may regulate neuronal apoptosis through activation of NF‐κB, β‐catenin or CREB signalling pathways . Other studies report that GSK‐3β can activate Nrf2 signalling to attenuate β‐amyloid‐induced oxidative stress in Alzheimer's disease models .…”
Section: Discussionmentioning
confidence: 99%